Pengaruh anestesi terhadap saturasi oksigen (SpO2) selama enterotomi pada kucing lokal (Felis domestica) - D. Noviana; M. Esrawati; G. Soedjono (Hemera Zoa, 2009)
The purpose of the research is to determine the influence of injection and inhalation anesthesia on oxygen saturation during enterotomy of Indonesian local cats (Felis domestica). Twelve local cats were divided into two groups. The first group (PI) received injection anesthesia with xylazin and ketamin, while the second group (P2) with the inhalation enesthetic isoflurane. Observations were made when the cat anesthetized with the observation interval every 15 minutes until the operation completed. The statistical test showed that oxygen saturation values in the provision of injection anesthesia and the inhalation anesthesia during enterotomy was not significantly different (P>0.05), however a decline in the value of injection anesthesia saturation was occured at minute 45 to 60. Both types of anesthesia caused significant decrease in the value of physiological parameters such as respiratory rate, heart rate and body temperature. Correlation test results showed that respiratory rate and body temperature were affecting the oxygen saturation during enterotomy. Oxygen saturation level during the inhalation anesthesia provide a relatively stable value when compared with the injection anesthesia, this is due to the supply of dissolved oxygen in inhalation anesthesia system.key words: anestesia, enterotomy, cats, oxygen, saturation.